Miejsce i znaczenie amerykańskich korporacji transnarodowych we współczesnej gospodarce globalnej - Sporek, Tadeusz; Kasperska-Sporek, Teresa (Place and Significance of American Transnational Corporations in the Contemporary Global Economy, 2005)
Well-intentioned calls for greater social responsibility by transnational corporations paradoxically may imperil the long-standing admonition against corporate interference in domestic political activities. Contemporary international society lacks a specific standard, or even a general consensus. regarding the permissible nature and extent of the political involvement of transnational corporations. Although intergovernmental documents generally proscribe the interference of transnational corporations in political matters, civil society groups increasingly urge corporate action that often constitutes political activity, sometimes in direct conflict with national government policies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1066, s. 361-372